Early Predictors of Remission in Acromegaly Patients after Pure Endoscopic Endonasal Transsphenoidal Surgery - Cetinalp, Nuri Eralp; Akkus, Gamze; Seydaoglu, Gulsah; Ozsoy, Kerem Mazhar; Akbaba, Mevlana; Baykara, Okay; Oktay, Kadir; Erman, Tahsin (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objective Surgery is the first-line treatment in acromegaly but it takes months to confirm remission. It is crucial to determine remission early in order to inform the patient and plan further treatment options. We aimed to evaluate the predictors of remission at the early phase after endoscopic endonasal pituitary surgery in acromegaly patients.Methods Fifty-four growth hormone (GH)-adenoma patients operated via pure endoscopic endonasal approach were analyzed in this observational study. We compared the basic clinical, radiological characteristics, and the preoperative and postoperative hormone levels in terms of remission according to current guidelines.Results The surgical remission rate was 61.1%. When the patients were compared according to surgical remission, the age, gender, and immunohistochemical granulation type were found to be nonsignificant, while diabetes mellitus was more common (55.6 vs. 44.4%). The preoperative tumor volume (1.2 ± 0.9 vs. 4.1 ± 4.2 cm3) and postoperative GH and insulin-like growth factor-1 (IGF-1) levels were higher in the nonremission group (p < 0.05). We defined a number of cut-off values of both GH and IGF-1 levels to predict remission at the postoperative phase. Age standardized regression analyses showed that postoperative day 1 (POD-1) GH levels (odds ratio [OR]: 8.9; 95% confidence interval [CI]: 1.99–40.0, p = 0.004) and tumor volume (OR: 3.14; 95% CI: 1.09–9.0, p = 0.034) were found to be significant independent predictors for remission.Conclusion We demonstrated that tumor volume and POD-1 GH levels are independent predictors of remission in acromegaly patients operated via the pure endoscopic endonasal technique and may be used as an early marker of remission, and this may lead to taking adjuvant medical therapies early into account to improve prognosis.
Keywords: acromegaly; remission; pituitary adenoma; endoscopic endonasal